2005
DOI: 10.1037/0893-164x.19.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between the SOGS-RA and the DSM-IV criteria for pathological gambling among youth.

Abstract: This study assessed the possible differences in the classification of adolescent gamblers when using the South Oaks Gambling Screen-Revised for Adolescents (SOGS-RA; K. C. Winters, R. D. Stinchfield, & J. Fulkerson, 1993) versus a clinical interview that was based on Diagnostic and Statistical Manual of Mental Disorders (DSM-IV; American Psychiatric Association, 1994) criteria for pathological gambling. A total of 631 adolescents ages 15-17 years participated in the two phases of the study. Results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…First, there has been controversy about the accuracy of the current instruments used to survey gambling behavior among adolescents (Derevensky, Gupta, & Winters, 2003b;Langhinrichsen-Rohling, Rohling, Rohde, & Seeley, 2004;Ladouceur, Ferland, Poulin, Vitaro, & Wiebe, 2005). However, the findings that criminal offender populations have higher levels of gambling related symptoms and a higher prevalence of problem gambling are robust across four jurisdictions among adults (Lahn, 2005) and this study found a similar phenomena with a comparison of adolescent juvenile offender populations and school populations using the same survey instrument.…”
Section: Discussionsupporting
confidence: 69%
“…First, there has been controversy about the accuracy of the current instruments used to survey gambling behavior among adolescents (Derevensky, Gupta, & Winters, 2003b;Langhinrichsen-Rohling, Rohling, Rohde, & Seeley, 2004;Ladouceur, Ferland, Poulin, Vitaro, & Wiebe, 2005). However, the findings that criminal offender populations have higher levels of gambling related symptoms and a higher prevalence of problem gambling are robust across four jurisdictions among adults (Lahn, 2005) and this study found a similar phenomena with a comparison of adolescent juvenile offender populations and school populations using the same survey instrument.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, SOGS is not validated in Finland [10,16], and a measure developed for adults is not the best choice for adolescents [26,27]. Nonetheless, these circumstances are systematic in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Hence, this study was not able to discriminate between participants with current disruptive gambling and those in remission. Some researchers have also cautioned that the DSM-IV criteria may represent a clinical definition of pathological gambling among adults rather than among youths (Ladouceur et al 2005). Fourth, this study did not examine cognitive biases in relation to specific gambling activities, despite research has found people using different cognitive heuristics/biases in skill and chance gambling games (Baboushkin et al 2001;Myrseth et al 2010).…”
Section: Limitations and Implicationsmentioning
confidence: 96%